Seed discontinuous hydration does not benefit germination, but improves drought tolerance of Triplaris gardneriana seedlings (Acta Scientiarum. Biological Sciences, 2021)
The discontinuous seed hydration enables the acquisition of tolerance to environmental stresses, causing a stress imprint. It may modify metabolic patterns and lead to improved stress responses. This study aims to evaluate the effects of discontinuous hydration on germination and on seedling growth of Triplaris gardneriana Wedd. under intermittent drought. The seeds have gone through cycles (0, 1, 2 and 3) of hydration and dehydration (HD). The seedlings produced were subjected to water deficit (daily watering and intervals of seven and fourteen days between watering). Seed germinability parameters and, relative growth rate (RGR) of seedling, leaf area, dry matter yield and leaf relative water content (RWC) were evaluated. The HD cycles did not benefit germination, but two HD cycles induced a better biomass accumulation and increased leaf area in seedlings under moderate water deficit, while three HD cycles promoted an increase in RGR and influenced the RWC values. Severe stress affects seedling growth, but subjection to HD cycles minimizes the deleterious effects of drought, suggesting discontinuous hydration acts leading stress imprint in plants.